The impact of lower caseloads in public employment services on the unemployed - René Böheim; Rainer Eppel; Helmut Mahringer (Journal for Labour Market Research, 2023)
In a randomised controlled trial in Austria, lowering caseloads for caseworkers in a Public Employment Office led to more meetings with unemployed clients, more job offers, more programme assignments, and more sanctions for noncompliance with job search requirements. It shortened unemployment spells through faster job entry, but also through more exits from the labour force in the 2 years following treatment. The duration of unemployment was reduced for a number of subgroups of the unemployed, but not all benefited from increased employment. For women and foreigners, lower caseloads led to more time out of the labour force. The quality of jobs after unemployment, measured by wages, did not change. A cost-benefit analysis suggests that lower caseloads not only shorten unemployment but also save public costs.
Keywords: J64; J68; 330; Active labour market policy; Public employment services; Caseworkers; Counselling; Job placement; Field experiment